The Importance of Continuing Monthly Fire Drills for the Preparedness of Crew Members at KM Spil Hapsri - Saputra, Bachtiar Bagus; Malik, Djamaludin; Anggraeny, Elva Febriana (Universitas Hang Tuah, 2024)
Continuing monthly Fire drills on commercial vessels such as the KM Spil Hapsri is very vital to ensure the alertness and safety of the ship's crew (ABK). Monthly Fire drills are not only a legal obligation, but also an effective strategy to reduce the risk of fire on commercial vessels. This research aims to explore the importance of monthly Fire drills on commercial ships, especially on KM Spil Hapsri. This research uses a qualitative descriptive method and uses data collection techniques by observation, interviews, literature study, and documentation study. The data sources used are primary and secondary data, data obtained from the place where the sailing practice is carried out, namely the KM Spil Hapsri ship. The theoretical basis used is the international rules of the Safety Of Life At Sea convention regarding the implementation of Fire drills. It was concluded that the implementation of the Fire drill at KM Spil Hapsri was previously carried out in accordance with the Regulations but stopped being carried out from August 2023 until the author finished carrying out the sailing practice, namely December 2023. If this continues, it could cause a decrease in the alertness of the ship's crew so that the ship's crew becomes less responsive in a fire situation and poses a risk of endangering the ship, cargo, and crew safety when a fire situation occurs